Factors contributing to delayed health insurance outpatient claims and administrative optimization strategies - Yurika (Journal of Evidence-based Nursing and Public Health, 2025)
Background: Pending claims in BPJS Kesehatan (National Health Insurance) systems can cause significant financial and administrative inefficiencies. At Universitas Indonesia Hospital, a notable number of outpatient health insurance claims remain unresolved, affecting both hospital revenue and claim processing performance. Methods: This study uses a cross-sectional observational approach, collecting data at one specific point in time to analyze pending outpatient health insurance claim files at Universitas Indonesia Hospital in 2023. Claim submission and verification procedures were examined, from medical record processing to claim file transfer to the insurer. Findings: Out of 102,530 outpatient claims submitted in 2023, 1,557 (1.5%) were pending, amounting to a total of IDR 1.84 billion. The main causes were incomplete files and medical resumes (47.1%), coding discrepancies and incorrect medical actions (38.1%), and indications of repeated actions (14.8%). Conclusion: The high rate of pending claims can be mitigated through targeted strategies such as increasing human resources in the support services unit, routine hardware maintenance, ongoing training for coders on the latest coding agreements, and better communication with doctors to ensure clarity in diagnosis documentation. Novelty/Originality of this article: This study offers an in-depth, institution-specific analysis of outpatient claim delays in a major Indonesian hospital, identifying root causes and practical solutions. It contributes to optimizing hospital administration and health insurance efficiency by addressing operational gaps often overlooked in broader policy discussions.